Pengaruh Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Pasien Pada Instalasi Rawat Inap Di Rsud Indrasari Rengat - Desi Wardiati; Zulkarnain; Any Widiyatsari (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2020)
The study was conducted at Indrasari Rengat Inhu Hospital. The aim is to determine the direct effect of the dimensions of service quality, namely Tangible, Emphaty, Reliability, Responseveness, Assurance on patient satisfaction and loyalty. This study took a sample of 100 patients. The variables used are Tangible, Emphaty, Reliability, Responseveness, Assurance of patient satisfaction and loyalty. Data were analyzed using SEM (Structural Equation Modeling) analysis which is operated through the Smart PLS 3.2.7 program. The results showed that there was an effect of Tangible, Emphaty, Reliability, Responseveness, Assurance on patient satisfaction. And there is the influence of Tangible, Emphaty, Reliability, Responseveness, Assurance on patient loyalty through patient satisfaction and there is an influence between patient satisfaction variables on patient loyalty, the better the patient satisfaction will increase patient loyalty.